Analisis Hubungan Antara Luas Panen Produksi Tenaga Kerja Pertanian Terhadap PDRB Di Kota Pontianak - Maswadi, Maswadi (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2017)
Agriculture is one of the economic vein in Indonesia. One important agricultural sector is food crops, the role of agriculture is evidenced by its effect on regional GDP. Gross Regional Domestic Revenue is the determinant of measuring regional economic development. The purpose of this study is to determine the effect of agricultural production factors such as land area, production, agricultural labor to GDRP in Pontianak. In this study, used secondary data collected from the Central Bureau of Statistics. This research uses descriptive analysis and multiple regression analysis using SPSS application. The results of this study are the productivity, production, and harvest area decreased every year due to land conversion. The main commodity production in the field of food plants, especially the most dominant vegetables in Pontianak City is spinach, mustard and kale. The best productivity in rice crops and crops is cassava. The influence of agriculture on the GDRP of Pontianak city is relatively stable from 2006 to 20012 and has increased in 2013. GRDP has a positive effect on labor, but negatively affects the area and agricultural production. Agricultural labor in Pontianak is relatively fluctuating per year.Key Word :GFRP, Labor, Land Area, Production